Desafios da promoção da equidade de gênero nas organizações: proposta de aplicação na Fundação Oswaldo Cruz - FIOCRUZ com base na experiência portuguesa - Way, Patrícia da Silva Von Der (2017)
Purpose: The present study addresses the emergence of labor relations between men and women; their diferences, mishaps, trajectory and challenges faced to reach professional development in private and public organizations. Design/Methodology: It seeks to answer, through a comparative study of initiatives in Brazil and in Portugal, how to promote gender equity in a public organization. Findings: The approaches to these experiences will lead to initiatives to promote gender equity at Fundação Oswaldo Cruz (Fiocruz), a public administration body in Brazil, to overcome the challenge of reducing historic-cultural inequality between men and women at work, and to leverage their professional development Research limitations: Gender Equity is a controversial subject often little addressed in organizations. Practical implications: It is necessary to know, to analyze, to revise concepts, to exchange information and experiences of best practices to improve knowledge, to discuss and to expand the involvement of people, workers, civil servants, and managers, for a path that provides development conditions for men and women professionally. Social implications: These proposals, if put into effect, can contribute to increase the degree of gender equality in a public organization in Brazil, which confirms Fiocruz as an innovative and an effective organization to tackle gender inequality and its resulting inequities. Originality: To our knowledge, this is the first study comparative study of initiatives in Brazil and in Portugal how to promote gender equity in a public organization. Keywords: gender equity, organizations, public administration, development opportunities for men and women. Paper category: Master’s thesis